2020
DOI: 10.1093/noajnl/vdaa011
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oncolytic adenovirus therapy overcomes tumor-induced immune suppression and sensitizes intracranial gliomas to anti-PD-1 therapy

Abstract: Background The tumor-selective human adenovirus Delta24-RGD is currently under investigation in phase II clinical trials for patients with recurrent glioblastoma (GBM). To improve treatments for patients with GBM, we explored the potential of combining Delta24-RGD with antibodies targeting immune checkpoints. Methods C57BL/6 mice were intracranially injected with GL261 cells and treated with a low dose of Delta24-RGD virus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…However, injection of a low dose of another oncolytic adenovirus, Delta24‐RGD, increases the density of intratumoral PD‐1 + T cells, which are inversely correlated with ex vivo T‐cell activity. In that study, low‐dose adenovirus was injected one time into gliomas 30 . By contrast, in this study, 5 × 10 5 PFU C‐REV was injected three times.…”
Section: Discussionmentioning
confidence: 88%
“…However, injection of a low dose of another oncolytic adenovirus, Delta24‐RGD, increases the density of intratumoral PD‐1 + T cells, which are inversely correlated with ex vivo T‐cell activity. In that study, low‐dose adenovirus was injected one time into gliomas 30 . By contrast, in this study, 5 × 10 5 PFU C‐REV was injected three times.…”
Section: Discussionmentioning
confidence: 88%
“…During the last decade or so, oncolytic viruses’ therapeutic usage has evolved from primarily antitumor cytotoxicity, toward enhancing the immune response [ 6 , 60 , 61 ]. The engineering of the oncolytic virus, and clinical trials [ 62 ] with oncolytic virus immunotherapy have provided early-stage results showing that some tumors respond by changing the “cold” tumor immune environment toward a “hot” one in response to the oncolytic virus [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of C57/BL6 mice bearing GL261 tumors with a systemic infusion of a GM-CSF-expressing reovirus followed by anti-PD-1 antibodies resulted in improved survival as compared to single-agent therapies. In-line with this, Belcaid et al recently demonstrated that low doses of the oncolytic adenovirus DNX-2401 (or Delta24-RGD) are sufficient to significantly alter the immune microenvironment in murine glioma, mostly by the upregulation of PD-1 and ICOS expression on CD8+ T cells [ 108 ]. Additionally, the brain tumor size was inversely correlated with the PD-1+ T-cell population in the tumor, suggesting that tumor regression is correlated with the local presence of PD-1+ T cells.…”
Section: Combination Therapy In Preclinical and Clinical Settingsmentioning
confidence: 99%
“…Additionally, the brain tumor size was inversely correlated with the PD-1+ T-cell population in the tumor, suggesting that tumor regression is correlated with the local presence of PD-1+ T cells. Indeed, Delta24-RGD, in combination with anti-PD-1, significantly improved the overall survival in GL261 and CT2A orthotopic mouse models [ 108 ].…”
Section: Combination Therapy In Preclinical and Clinical Settingsmentioning
confidence: 99%